PENANAMAN MANGROVE SEBAGAI UPAYA PELESTARIAN EKOSISITEM PESISIR DI GAMPONG LAMTUTUI, PEUKAN BADA, KABUPATEN ACEH BESAR PROVINSI ACEH - Rika Astuti; Eka Lisdayanti (Marine Kreatif, 2022)
Mangroves are biological natural resources that have the potential to provide benefits for human life and aquatic biota organisms. Mangrove ecosystems have ecological and economic functions in coastal areas. The Gampong Lamtutui area has an important role because it is a provider of natural resources and environmental services with great potential in terms of ecology, economy and tourism. So far, the activities that occur in the mangrove ecosystem area in Lamtutui have an unfavorable impact on the mangrove vegetation in that location, due to the large number of uses of the mangrove area for vannamei shrimp pond areas, so that the structure of mangrove vegetation at various growth levels changes. The purpose of this service is to raise awareness and motivation for the coastal communities of Gampong Lamtutui to replant mangroves as a form of concern for the preservation of coastal ecosystems. This service activity is carried out for two days, from October 30, 2021 to October 31, 2021. The location of this service is in Gampong Lamtutui, Peukan Bada District, Aceh Besar Regency. The method of activity used in this activity is counseling and mentoring mangrove planting. The results of this service activity are the planting of 1,000 stems of Rhizophora sonneratia mangrove tree seeds in Gampong Lamtutui, as well as the establishment of cooperation with a group of local fishermen for monitoring the mangrove trees that have been planted.